THE REPRESENTATION OF INDONESIAN NATIONAL IDENTITY IN SYUHADA MOSQUE, KOTABARU, YOGYAKARTA - Mardhiyah, Muthia Zahri; Akbar, Ali (UI Scholars Hub, 2025)
This article examines the concept of national identity as embodied by the Syuhada Mosque, located in Kotabaru, Yogyakarta. Completed in 1952, the mosque was established as a monument to the independence of the Republic of Indonesia. This research addresses whether Syuhada Mosque genuinely represents national identity. The study aims to describe the architectural form of Syuhada Mosque and elucidate the representations of national identity embedded within its structure. The research methodology aligns with the framework proposed by Sharer and Ashmore, encompassing formulation, implementation, data collection, data processing, analysis, interpretation, and publication. Based on its historical background, the foundational ideas and concepts of its founders, and its contextual relationship with the surrounding environment, Syuhada Mosque primarily functions as a mosque that symbolizes Indonesian independence and unity. Furthermore, the Syuhada Mosque inherently embodies Islamic and traditional values typical of a mosque while demonstrating an adaptive integration with its surrounding architectural landscape.